EGFR phosphorylates FAM129B to promote Ras activation - Ji, Haitao (Proc Natl Acad Sci U S A, 2016)
Ras GTPase-activating proteins (GAPs) are important regulators for Ras activation, which is instrumental in tumor development. However, the mechanism underlying this regulation remains elusive. We demonstrate here that activated EGFR phosphorylates the Y593 residue of the protein known as family with sequence similarity 129, member B (FAM129B), which is overexpressed in many types of human cancer. FAM129B phosphorylation increased the interaction between FAM129B and Ras, resulting in reduced binding of p120-RasGAP to Ras. FAM129B phosphorylation promoted Ras activation, increasing ERK1/2- and PKM2-dependent β-catenin transactivation and leading to the enhanced glycolytic gene expression and the Warburg effect; promoting tumor cell proliferation and invasion; and supporting brain tumorigenesis. Our studies unearthed a novel and important mechanism underlying EGFR-mediated Ras activation in tumor development.